Evidence-Based Homoeopathic Treatment of Acute Herpes Zoster (Shingles): A Case Report - Gupta, Yogeshwari; Pandey, Khushbu (Homœopathic Links, 2021)
Herpes zoster (HZ), also known as shingles, occurs due to reactivation of varicella zoster. It is manifested by unilateral, painful, vesicular rashes following a dermatome. Homoeopathy is well known for its tremendous results in chronic cases. This article presents the evidence-based significant result of single homoeopathic remedy in an acute case of HZ within a short time period without any post-herpetic neuralgia which usually follows the HZ for months. Three to four doses of Hypericum 30 CH provided significant relief within a day and complete recovery within 10 days. Modified Naranjo score is 9, indicating definite causal attribution. This case proves that by selecting appropriate similimum, promising and positive results are achieved by homoeopathy, be it acute or chronic cases in a safe and gentle way. No such existing homoeopathic literature provides any characteristic information particularly related to HZ in Hypericum. So, future research and clinical trials could be beneficial for better validation of Hypericum as a therapeutic for HZ.
Keywords: herpes zoster; homoeopathy; shingles